Answer:
(h o k)(3) = 3
(k o h)(-4b) = -4b
Step-by-step explanation:
If f(x) and g(x) are inverses, then (f o g)(x) = (g o f)(x) = x
(h o k)(3) = 3
(k o h)(-4b) = -4b
Answer:
3/5
Step-by-step explanation:
sohcahtoa
since we're finding sine, we need the opposite and hypotenuse.
opposite of <A=3, hyp of <A=5.
opp comes before hyp in "soh", so sin<A=3/5
Rectangular form:
z = -2.1213203-2.1213203i
Angle notation (phasor):
z = 3 ∠ -135°
Polar form:
z = 3 × (cos (-135°) + i sin (-135°))
Exponential form:
z = 3 × ei (-0.75) = 3 × ei (-3π/4)
Polar coordinates:
r = |z| = 3 ... magnitude (modulus, absolute value)
θ = arg z = -2.3561945 rad = -135° = -0.75π = -3π/4 rad ... angle (argument or phase)
Cartesian coordinates:
Cartesian form of imaginary number: z = -2.1213203-2.1213203i
Real part: x = Re z = -2.121
Imaginary part: y = Im z = -2.12132034
We are given the following function and want to find the y-intercept:
![f(x)=2(x-7)^2-32](https://tex.z-dn.net/?f=f%28x%29%3D2%28x-7%29%5E2-32)
Just substitute the value x=0 into the equation to find the value of the y-intercept:
![y=2(0-7)^2-32](https://tex.z-dn.net/?f=y%3D2%280-7%29%5E2-32)
Simplify
![=2(49)-32](https://tex.z-dn.net/?f=%3D2%2849%29-32)
Simplify again
![=66](https://tex.z-dn.net/?f=%3D66)
Since the value of f(x), or y, when x=0 is 66, the y-intercept of this function is 66.
Let me know if you need any clarifications, thanks!
~ Padoru